Governing the Global Value Chain: GLOBALGAP and the Chilean Fresh Fruit Industry - Bain, Carmen (The International Journal of Sociology of Agriculture and Food, 2010)
An important argument within the agri-food literature is that power within the value chain has shifted from producers to global supermarkets chains. An example of this is GLOBALGAP, a standards and certification scheme launched by a handful of UK and European supermarkets, which allows them to govern their global value chains. This case study draws on in-depth interviews to understand how large-scale producers and exporters within the Chilean fresh fruit export sector have responded to GLOBALGAP. Rather than accept the role of standards takers, the organizational leadership of this sector has integrated itself within the decision-making structures of GLOBALGAP as standards makers. From their perspective, GLOBALGAP is a tool that will help consolidate and advance their position as world leaders in the export of fresh fruits. While the rising power of retailers is extraordinary, this study demonstrates that we cannot ignore how large-scale producers and exporters are also positioning themselves to negotiate, lead, and advance their own interests.